Colored adhesive tape
By adopting a specific lamination structure and material composition in the adhesive sheet, the problem of unstable gloss value of the matte layer in the existing technology is solved, a more uniform surface and stable gloss value are achieved, and the performance and appearance of the product are improved. quality.
Patent Information
- Application Number
- CN202480003207.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-31
- Filing Date
- 2024-01-29
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, the gloss value of the matte layer of the adhesive sheet is unstable, mainly due to the roughness of the surface of the black colored layer, making it difficult to obtain a uniform matte effect.
It adopts a structure of a peeling film, an adhesive layer, a colored layer, a resin film layer and a matting layer laminated in sequence. The matting layer is composed of polyester resin, isocyanate and silica, with a thickness of 0.5 μm or more and 3 μm or less. The coloring layer contains Carbon black pigment.
It achieves a colored adhesive tape with a more uniform surface and stable gloss value, avoids the problem of surface roughness caused by the action of solvents, and improves the design and anti-fouling properties of the product.
Smart Images

Figure CN119365557A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a colored adhesive tape. Background Art
[0002] In the past, colored films and colored adhesive tapes have been used in various industrial fields for the purposes of decoration, display, concealment, reflection, and shading. Among them, in portable electronic terminals such as personal computers, digital cameras, electronic notepads, mobile phones, PHS (Personal Handyphone System, Xiaolingtong), smart phones, game consoles, and electronic books, especially in the field with high requirements for miniaturization and thinness, various colored adhesive tapes are used from the perspective of reducing the number of parts used while taking into account the shading effect based on black coloring, the improvement of brightness based on white coloring, the masking of defects in the appearance of parts (uneven depth (Japanese: ムラ), point defects (Japanese: point defect)), etc.), and the improvement of appearance while fixing and protecting parts. In addition, in portable electronic terminals, adhesive sheets are sometimes used for the purpose of protecting graphite sheets provided for heat dissipation purposes (for example, refer to Patent Document 1.).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent No. 6789013 Summary of the invention
[0006] Problems to be solved by the invention
[0007] However, the adhesive sheet described in Patent Document 1 has a matte layer on the outermost layer, and has a laminated structure of "matte layer / black coloring layer / PET film / adhesive layer / peeling film". The adhesive sheet having such a laminated structure of "matte layer / black coloring layer / PET film / adhesive layer / peeling film" forms the matte layer by applying a resin that becomes a matte layer by gravure printing on the black coloring layer. Therefore, when forming the matte layer, there is a problem that the surface of the black coloring layer becomes rough due to the solvent, and it is difficult to obtain a matte layer with a uniform surface. Therefore, the gloss value of the matte layer becomes unstable.
[0008] The present invention has been made in view of the above-mentioned aspects, and an object of the present invention is to provide a colored pressure-sensitive adhesive tape having a more uniform surface and a stable gloss value.
[0009] Means for solving problems
[0010] According to a colored adhesive tape involved in one embodiment of the present invention, there is provided a colored adhesive tape, which is a colored adhesive tape in which a release film, an adhesive layer, a colored layer, a resin film layer and a matte layer are sequentially stacked, wherein the matte layer is a layer having a polyester resin, an isocyanate and a matte agent as main components, the matte agent contains silicon dioxide, and has a thickness of 0.5 μm to 3 μm, and the colored layer is a layer having a resin, an isocyanate and a pigment containing carbon black as main components.
[0011] Effects of the Invention
[0012] According to one aspect of the present invention, a colored adhesive tape having a more uniform surface and a stable gloss value can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a cross-sectional view schematically showing an example of a colored pressure-sensitive adhesive tape according to an embodiment of the present invention.
[0014] Figure 2 This is a cross-sectional view schematically showing an example in which the colored pressure-sensitive adhesive tape according to one embodiment of the present invention is applied to a heat dissipation sheet or a magnetic sheet. DETAILED DESCRIPTION
[0015] Next, one embodiment of the present invention will be described below with reference to the drawings.
[0016] Here, the accompanying drawings are schematic illustrations, and the relationship between thickness and plane size, the ratio of thickness of each layer, etc. are different from the actual situation. In addition, the embodiments shown below are embodiments for illustrating the configuration for concretizing the technical idea of the present invention. In the technical idea of the present invention, the material, shape, structure, etc. of the constituent parts are not specific to the following contents. The technical idea of the present invention can be variously modified within the technical scope specified by the technical solution recorded in the claims.
[0017] (Constitution of Colored Adhesive Tape)
[0018] Figure 1 1 is a cross-sectional view schematically showing a colored adhesive tape 1 according to one embodiment of the present invention. Figure 1 As shown, the colored adhesive tape 1 includes a matte layer 2, a resin film layer 3, a colored layer 4, an adhesive layer 5, and a release film 6. The colored adhesive tape 1 is formed by laminating the above layers in order from the release film 6 side.
[0019] (matt layer)
[0020] The matt layer 2 is a layer having polyester resin, isocyanate and matting agent as main components, and containing silicon dioxide as a matting agent. As isocyanate, for example, aliphatic isocyanate such as HDI (hexamethylene diisocyanate) can be used. By including isocyanate in the matt layer 2, the adhesion with the resin film layer 3 as the substrate can be improved. From the viewpoint of obtaining a sufficient matte feeling, the thickness of the matt layer 2 is preferably 0.5 μm or more. In addition, although there is no upper limit to the thickness of the matt layer 2, if it is 3 μm, a sufficient matte feeling is obtained, so it is preferably 3 μm or less.
[0021] It should be noted that in this specification, the component that accounts for 50% by weight or more of the components in the layer is referred to as the main component, and "polyester resin, isocyanate and matting agent as main components" means that the total content of polyester resin, isocyanate and matting agent exceeds 50% by weight of the components in the layer.
[0022] The matte layer 2 may be uncolored or colored. By coloring the matte layer 2, the design of the colored adhesive tape 1 can be improved. When the matte layer 2 is colored, for example, a pigment is mixed in a coating material for forming the matte layer 2 having a polyester resin, an isocyanate, and a matting agent as main components to perform coloring.
[0023] As a matting agent, barium sulfate is sometimes used, for example. However, when only barium sulfate is added as a matting agent to the coating for forming the matting layer 2, if the matting layer 2 is directly applied to the resin film layer 3 containing PET resin described later, it is difficult to produce a matte feeling. In addition, since barium sulfate has a high specific gravity and is easy to precipitate, it is difficult to apply it, and the particle size is also small, in order to produce a matte feeling, a large amount of barium sulfate needs to be added. In this embodiment, since silicon dioxide with a low specific gravity and a large particle size is used as a matting agent, a matte feeling can be fully produced with a smaller addition amount.
[0024] The 60° gloss value of the surface of the matt layer 2 on the opposite side to the resin film layer 3 is preferably 3 or less. The surface with the gloss value limited in this way can be a surface with alcohol resistance. "Having alcohol resistance" means: when exposed to alcohol (such as ethanol), the surface can suppress the change of the appearance of the surface (such as the change of the gloss value, color tone (Japanese: color taste) or light shielding property). Therefore, when the surface of the colored adhesive tape 1, that is, the surface of the matt layer 2 on the opposite side to the resin film layer 3 is contaminated, the contamination can be wiped off with alcohol without worrying about reducing the design. Therefore, antifouling property and design can be ensured.
[0025] In order to impart antifouling properties to the colored pressure-sensitive adhesive tape 1, the water contact angle of the surface of the matte layer 2 opposite to the resin film layer 3 is preferably 80° or more. The water contact angle may be measured using a commercially available contact angle measuring device in accordance with JIS R 3257: 1999. For example, the measurement may be performed under the following conditions.
[0026] Water contact angle measurement conditions
[0027] Measuring device: Contact angle measuring instrument FACE CA-X (manufactured by Kyowa Interface Chemical Co., Ltd.)
[0028] Measurement atmosphere: 23°C, 50% RH
[0029] Test liquid: distilled water
[0030] Measurement time: 1500ms after adding
[0031] (resin film layer)
[0032] The resin film layer 3 is a layer used as a base material, and is not particularly limited. For example, it is formed of PET (polyethylene terephthalate) resin, PI (polyimide) resin, etc. If the thickness of the resin film layer 3 is 1 μm or more, the colored layer and the matte layer can be well laminated. In addition, if the thickness of the resin film layer 3 is 3 μm or less, the colored adhesive tape 1 has sufficient flexibility, so it can be finely processed when used. The width of the resin film layer 3 is not limited, and for example, it has a width of 1050 mm.
[0033] (Coloring layer)
[0034] The coloring layer 4 is a black coloring layer, which contains resin, isocyanate and a pigment containing carbon black as main components. As the resin, a polyester resin or an acrylic resin is preferred. As the isocyanate, for example, an aliphatic isocyanate such as HDI (hexamethylene diisocyanate) can be used. By including isocyanate in the coloring layer 4, the adhesion with the resin film layer 3 can be improved. The coloring layer 4 contains known carbon black as a colorant. It should be noted that, for the purpose of color matching of the coloring layer 4, colorants of other colors may also be included.
[0035] In addition, “containing resin, isocyanate and pigment including carbon black as main components” means that the total content of the resin, isocyanate and pigment including carbon black exceeds 50% by weight of the components in the layer.
[0036] From the viewpoint of ensuring sufficient concealment, the coloring layer 4 preferably has a thickness of 2 μm or more and 4 μm or less. When the thickness of the coloring layer 4 is 4 μm or more, the degree of change in concealment due to its thickness is small, and the change in concealment obtained with respect to the increase in the thickness of the coloring layer 4 is small. Therefore, by setting the thickness of the coloring layer 4 to 2 μm or more and 4 μm or less, the increase in the thickness of the coloring layer 4 can be suppressed and sufficient concealment can be obtained.
[0037] (Adhesive layer)
[0038] The adhesive constituting the adhesive layer 5 is not particularly limited, and examples thereof include acrylic adhesives, urethane adhesives, synthetic rubber adhesives, polyester adhesives, silicone adhesives, etc. Among them, acrylic adhesives containing (meth)acrylic polymers are preferred from the viewpoint of easy adjustment of molecular weight, crosslinking degree, etc., and excellent heat resistance, weather resistance, cost, etc.
[0039] The (meth)acrylic acid-based polymer is a polymer containing a structural unit derived from a (meth)acrylic acid-based monomer.
[0040] The (meth)acrylic acid monomer is not particularly limited, and examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, isomyristyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, etc. These (meth)acrylic acid monomers may be used alone or in combination of two or more.
[0041] The (meth)acrylic polymer preferably further contains a structure derived from a crosslinkable functional group-containing monomer.
[0042] By making the (meth)acrylic polymer contain the structure derived from the crosslinkable functional group-containing monomer, the cohesive force of the adhesive layer 5 can be adjusted by crosslinking the crosslinkable functional group, thereby improving heat resistance. The crosslinkable functional group may be crosslinked or not, but is preferably crosslinked. However, even in the state of a non-crosslinked structure, the cohesive force of the adhesive layer 5 can be improved by the interaction between the functional groups.
[0043] As the above-mentioned crosslinking functional group-containing monomer, for example, there can be mentioned: monomers containing carboxyl, hydroxyl, epoxy, double bond, triple bond, amino, amide, nitrile, etc. These crosslinking functional group-containing monomers can be used alone or in combination of two or more. Among them, preferably at least one selected from carboxyl-containing monomers and hydroxyl-containing monomers. From the aspect of being easy to adjust the heat resistance of the above-mentioned adhesive layer 5 by crosslinking based on isocyanate-based crosslinking agents, hydroxyl-containing monomers are more preferred.
[0044] It should be noted that the crosslinkable functional group-containing monomer may further contain an alkyl group, an ether group, a carbonyl group, an ester group, a carbonate group, an amide group, a carbamate group, and the like.
[0045] Examples of the carboxyl group-containing monomer include (meth)acrylic acid and other (meth)acrylic acid monomers. Examples of the hydroxyl group-containing monomer include (meth)acrylate 4-hydroxybutyl, (meth)acrylate 2-hydroxyethyl, etc. Examples of the epoxy group-containing monomer include (meth)acrylate glycidyl, etc. Examples of the double bond-containing monomer include (meth)acrylate allyl, hexanediol di(meth)acrylate, etc. Examples of the triple bond-containing monomer include (meth)acrylate propargyl, etc. Examples of the amide group-containing monomer include (meth)acrylamide, etc.
[0046] In the (meth)acrylic polymer, the content of the structure derived from the monomer having a crosslinkable functional group is not particularly limited, but from the viewpoint of adjusting the adhesive force and heat resistance of the adhesive layer 5, the preferred lower limit of the content of the structural unit is 0.05% by weight, and the preferred upper limit is 30% by weight. The more preferred lower limit of the content of the structural unit is 0.1% by weight, and the more preferred upper limit is 25% by weight.
[0047] In addition, in the (meth)acrylic polymer, the content of the structure derived from the hydroxyl-containing monomer is not particularly limited, but from the viewpoint of adjusting the adhesive force and heat resistance of the adhesive layer 5, the preferred lower limit of the content of the structural unit is 0.05% by weight, and the preferred upper limit is 5% by weight. The more preferred lower limit of the content of the structural unit is 0.08% by weight, and the more preferred upper limit is 1% by weight.
[0048] The (meth)acrylic polymer preferably includes a structural unit derived from a monomer containing biogenic carbon. By making the (meth)acrylic polymer include a structural unit derived from a monomer containing biogenic carbon, the content of biogenic carbon in the adhesive layer 5 is increased, and the environmental load caused by the obtained adhesive tape can be further reduced.
[0049] In the present specification, “containing biogenic carbon” means that the biogenic carbon content of the compound measured according to ASTM D6866-22 is 1% or more.
[0050] In order to obtain the above-mentioned (meth)acrylic acid polymer, a monomer mixture containing the above-mentioned (meth)acrylic acid monomer, the above-mentioned crosslinkable functional group-containing monomer, etc., may be subjected to a free radical reaction in the presence of a polymerization initiator to perform copolymerization. As a method for subjecting the above-mentioned monomer mixture to a free radical reaction, that is, a polymerization method, a conventionally known method may be used, for example, solution polymerization (boiling point polymerization or constant temperature polymerization), emulsion polymerization, suspension polymerization, bulk polymerization, etc.
[0051] The weight average molecular weight (Mw) of the (meth)acrylic polymer is not particularly limited, but the upper limit is preferably 2 million. If the weight average molecular weight (Mw) is 2 million or less, the initial adhesion to the adherend is good even if the adhesive layer 5 is thin. The upper limit of the weight average molecular weight (Mw) is more preferably 1.5 million, and the upper limit is further preferably 1.3 million.
[0052] The lower limit of the weight average molecular weight (Mw) is not particularly limited, but is preferably 400,000, and more preferably 500,000, from the viewpoint of the adhesive strength and shape retention of the adhesive layer 5 .
[0053] It should be noted that the weight average molecular weight of the (meth)acrylic acid-based polymer can be obtained, for example, by using the GPC (Gel Permeation Chromatography) method in terms of standard polystyrene. More specifically, for example, the measurement can be performed using the "2690 Separations Module" manufactured by Water Corporation as a measuring device, the "GPC KF-806L" manufactured by Showa Denko K.K. as a chromatographic column, ethyl acetate as a solvent, a sample flow rate of 1 mL / min, and a column temperature of 40°C.
[0054] The adhesive layer 5 may contain a tackifier resin.
[0055] Examples of the tackifying resin include rosin ester resins, hydrogenated rosin resins, terpene resins, terpene phenol resins, coumarone indene resins, alicyclic saturated hydrocarbon resins, C5 petroleum resins, C9 petroleum resins, C5-C9 copolymerized petroleum resins, etc. These tackifying resins may be used alone or in combination of two or more.
[0056] The content of the above-mentioned tackifier resin is not particularly limited, but from the viewpoint of having good initial adhesion to the adherend even if the above-mentioned adhesive layer 5 is relatively thin and exerting sufficient adhesive force, the preferred upper limit is 50 parts by weight, the preferred lower limit is 10 parts by weight, the more preferred upper limit is 35 parts by weight, and the more preferred lower limit is 20 parts by weight, relative to 100 parts by weight of the resin (for example, (meth) acrylic polymer) which is the main component of the above-mentioned adhesive layer 5.
[0057] The adhesive layer 5 can be crosslinked by a crosslinking agent. The crosslinking agent is not particularly limited and can be appropriately selected according to the adhesive constituting the adhesive layer 5. For example, when the adhesive constituting the adhesive layer 5 is an acrylic adhesive, as a crosslinking agent, for example, isocyanate crosslinking agents, epoxy crosslinking agents, aziridine crosslinking agents, metal chelate crosslinking agents, etc. can be cited. Among them, from the aspect of making the adhesion of the adhesive tape to the adherend more excellent, any of isocyanate crosslinking agents, aziridine crosslinking agents, and epoxy crosslinking agents are preferred, and isocyanate crosslinking agents are preferred. They can be used alone or in combination of two or more. As commercial products of isocyanate crosslinking agents, for example, Coronate HX (manufactured by Japan Polyurethane Co., Ltd.) and Takenate D-101E (manufactured by Mitsui Chemicals Co., Ltd.) can be cited. As commercial products of epoxy crosslinking agents, for example, TETRAD-C and TETRAD-X (manufactured by Mitsubishi Gas Chemical Co., Ltd.) can be cited. Examples of commercially available products of the metal chelate cross-linking agent include Aluminum chelate A (manufactured by Kawaken Fine Chemical Co., Ltd.).
[0058] The content of the crosslinking agent is not particularly limited, but the preferred lower limit is 0.1 parts by weight, the preferred upper limit is 5 parts by weight, the more preferred lower limit is 0.3 parts by weight, and the more preferred upper limit is 3 parts by weight, relative to 100 parts by weight of the adhesive solid content.
[0059] The adhesive layer 5 may further contain known additives such as inorganic fillers such as fumed silica, colorants such as pigments, plasticizers, resins, surfactants, waxes, particulate fillers, etc. These additives may be used alone or in combination of two or more.
[0060] The gel fraction of the adhesive layer 5 is not particularly limited, but the preferred lower limit is 10% by weight, and the preferred upper limit is 70% by weight. If the gel fraction is 10% by weight or more, the heat resistance of the adhesive layer 5 is improved. If the gel fraction is 70% by weight or less, even if the adhesive layer 5 is thin, sufficient adhesive force is exerted. The more preferred lower limit of the gel fraction is 15% by weight, the more preferred upper limit is 65% by weight, the further preferred lower limit is 20% by weight, and the further preferred upper limit is 60% by weight.
[0061] In addition, the gel fraction of the adhesive layer 5 can be measured by the following method.
[0062] Only 0.1 g of the adhesive layer (adhesive composition) was taken out from the colored adhesive tape, immersed in 50 mL of ethyl acetate, and shaken for 24 hours at 23 degrees and 200 rpm using a shaker. After shaking, the ethyl acetate and the adhesive composition that had swollen after absorbing the ethyl acetate were separated using a metal mesh (mesh size #200). The separated adhesive composition was dried at 110°C for 1 hour. The weight of the adhesive composition containing the metal mesh after drying was measured, and the gel fraction of the adhesive layer was calculated using the following formula (1).
[0063] Gel fraction (weight %) = 100 × (W1-W2) / W0... (1)
[0064] (W0: initial weight of adhesive composition, W1: weight of adhesive composition containing metal mesh after drying, W2: initial weight of metal mesh)
[0065] However, when the adhesive layer cannot be completely dissolved by ethyl acetate, a solvent such as toluene, hexane, or water is used instead of ethyl acetate. Specifically, for example, when the adhesive layer contains a styrene elastomer, toluene or hexane is used, and when the adhesive layer contains polyvinyl alcohol, hot water at 90° C. is used.
[0066] The glass transition temperature (Tg) of the adhesive layer 5 is not particularly limited, but from the viewpoint of good adhesion even when the thickness of the adhesive layer 5 is thin and heat resistance, the preferred lower limit is -70°C and the preferred upper limit is 25°C. The more preferred lower limit of the glass transition temperature (Tg) is -65°C and the more preferred upper limit is 15°C.
[0067] It should be noted that the glass transition temperature (Tg) of the above-mentioned adhesive layer 5 can be obtained as follows. For example, the storage modulus G' and loss modulus G" at each temperature can be measured under the following conditions using a polymer dynamic viscoelasticity measuring device "itkDVA-200" (manufactured by IT Measurement and Control Co., Ltd.), tanδ at each temperature can be calculated, and the temperature at which tanδ reaches a peak value can be obtained as the glass transition temperature (Tg).
[0068] Measurement mode: Shear
[0069] Heating rate: 5℃ / min
[0070] Measuring temperature range: -30℃~150℃
[0071] Set strain: 0.1%
[0072] Vibration frequency: 1Hz
[0073] The thickness of the adhesive layer 5 is not particularly limited, but preferably the lower limit is 1 μm and the upper limit is 4 μm. If the thickness of the adhesive layer 5 is less than 1 μm, the adhesiveness of the adhesive layer 5 may sometimes decrease and peel off from the adherend. If the thickness of the adhesive layer 5 exceeds 4 μm, the colored adhesive tape 1 may sometimes become thick and may not be suitable for use in portable electronic terminals. A more preferable lower limit of the above thickness is 1.5 μm, and a more preferable upper limit is 3.5 μm.
[0074] (Release film)
[0075] The release film 6 is used to protect the adhesive layer 5 before use, and its material is not particularly limited. The surface of the release film 6 on the side in contact with the adhesive layer 5 is a surface on which a release treatment has been performed, and is composed of, for example, a PET film coated with a silicone release agent. In addition, the average height Rc of the roughness curve elements (Japanese: 粗さ曲線要素) of the surface of the release film 6 on the side opposite to the adhesive layer 5 is preferably greater than 500 nm. By making the average height Rc of the roughness curve elements greater than 500 nm, the frictional force with the roller during the conveyance of the colored adhesive tape 1 is reduced, and the generation of meandering and wrinkles can be suppressed.
[0076] (Colored adhesive tape)
[0077] By setting the total film thickness of the colored adhesive tape 1 to 4.5 μm or more, the film thickness required to exhibit the functions of each layer constituting the tape can be ensured. In addition, the total film thickness of the colored adhesive tape 1 is preferably 13 μm or less, and more preferably 10 μm or less. Thereby, the bonding of fine components can be performed precisely. It should be noted that the total film thickness of the colored adhesive tape 1 mentioned here refers to the thickness of the laminate 1' as a whole, which includes the adhesive layer 5, the colored layer 4, the resin film layer 3, and the matte layer 2, excluding the release film 6.
[0078] Regarding the colored adhesive tape 1, from the viewpoint of obtaining sufficient light-shielding properties and concealment properties of the adherend, in the laminate constituting the colored adhesive tape 1, the light transmittance of the laminate 1' including the matte layer 2, the resin film layer 3, the colored layer 4, and the adhesive layer 5, excluding the release film 6, is preferably 5% or less. Such a colored adhesive tape 1 can appropriately reflect the hue of the adherend (for example, a graphite sheet), and thereby impart the desired hue, texture, and design.
[0079] The colored adhesive tape 1 having such a configuration is extremely thin and has good heat resistance. Therefore, as shown, for example, Figure 2 by pasting the adhesive layer 5 side of the colored adhesive tape 1' in a state where the release film 6 has been peeled off from the colored adhesive tape 1 onto the surface of a heat sink or a magnetic sheet 10 attached to an electronic component that generates heat during use, it can be particularly suitable for use as a tape for surface protection.
[0080] (Method for producing colored adhesive tape)
[0081] The method for producing the colored pressure-sensitive adhesive tape 1 is not particularly limited, and examples thereof include the following methods.
[0082] First, the colored layer 4 is formed on one surface of the resin film layer 3. For example, a colored layer coating material containing carbon black is applied to one surface of the resin film layer 3 by gravure printing or the like to form the colored layer 4.
[0083] Next, a matte layer coating material is applied to the other surface of the resin film layer 3 by gravure printing or the like to form the matte layer 2 .
[0084] Next, the adhesive layer 5 is formed by casting or the like on the release-treated surface of the release film 6. Examples of the casting method include a method in which a resin solution to be the adhesive layer 5 is applied by gravure coating, roll coating or the like, followed by heating and drying.
[0085] Next, the surface of the color layer 4 opposite to the resin film layer 3 is bonded to the surface of the adhesive layer 5 opposite to the release film 6 .
[0086] Thus, the colored pressure-sensitive adhesive tape 1 in which the release film 6 , the pressure-sensitive adhesive layer 5 , the colored layer 4 , the resin film layer 3 , and the matte layer 2 are laminated in this order is formed.
[0087] (Effects of the Colored Adhesive Tape According to the Embodiment)
[0088] The colored adhesive tape 1 forms a matte layer 2 on one surface of the resin film layer 3 and a colored layer 4 on the other surface. Therefore, it is possible to avoid the situation where the surface of the colored adhesive tape 1, that is, the surface of the matte layer 2 on the opposite side of the resin film layer 3, becomes an uneven surface, and obtain a colored adhesive tape 1 with a uniform surface. That is, if the colored adhesive tape is formed into a laminated structure such as "matte layer 2 / colored layer 4 / resin film layer 3 / adhesive layer 5 / peeling film 6", when the colored layer 4 is formed on the resin film layer 3 and the coating for forming the matte layer 2 is further applied on the colored layer 4 by gravure printing, the surface of the colored layer 4 will become rough due to the solvent contained in the coating for forming the matte layer 2, and as a result, the surface of the matte layer 2 formed on the colored layer 4 may become uneven, or the gloss value may become unstable. In contrast, in the present embodiment, the colored adhesive tape 1 is a structure in which "matte layer 2 / resin film layer 3 / colored layer 4 / adhesive layer 5 / peeling film 6" are laminated in sequence. Therefore, one surface of the matt layer 2 becomes the surface of the colored adhesive tape 1, and the matt layer 2 is formed on the resin film layer 3. The surface of the resin film layer 3 is flat, and when the matt layer 2 is formed on the surface of the resin film layer 3, the possibility of the surface of the resin film layer 3 becoming rough is low. Therefore, it is possible to avoid the situation where the surface of the matt layer 2 formed on the surface of the resin film layer 3 becomes uneven due to the surface shape of the resin film layer 3, and as a result, a colored adhesive tape with a uniform surface on the matt layer 2 side can be obtained.
[0089] In addition, as a method for preventing unevenness on the surface of the colored adhesive tape, a method of obtaining a matte feeling by adding a matting agent to the colored layer without providing the matting layer 2 is also considered. However, in this case, the gloss value of the colored layer is unstable, and the matting agent in the colored layer is mixed with the pigment. Therefore, there is a problem that the gloss value of the colored layer is easily changed depending on the layer thickness of the colored layer and the drying method of the colored layer.
[0090] In addition, when the colored adhesive tape is formed into a laminated structure of "resin film layer 3 / coloring layer 4 / adhesive layer 5 / peeling film 6" without providing the matte layer 2, a matte feeling cannot be obtained. When the colored adhesive tape is formed into a laminated structure of "matte layer 2 / resin film layer 3 / adhesive layer 5 with added colorant / peeling film 6", it is difficult to achieve both adhesive performance and black concentration in the adhesive layer 5. In addition, when the colored adhesive tape is formed into a laminated structure of "matte layer 2 / resin film layer 3 with added colorant / adhesive layer 5 / peeling film 6", there is a problem that a sufficient black concentration cannot be obtained.
[0091] As described above, the colored adhesive tape 1 in the present embodiment can obtain a colored adhesive tape having a uniform surface shape by laminating the layers in an appropriate order without adding a colorant to other layers.
[0092] Example
[0093] Hereinafter, examples of the colored pressure-sensitive adhesive tape according to the present invention will be described.
[0094] It should be noted that the present invention is not limited to the following examples.
[0095] In the following steps, as colored adhesive tapes for evaluation, colored adhesive tapes of Examples 1 to 12 and Comparative Examples 1 to 3 were prepared and evaluated. The configurations of the colored adhesive tapes for evaluation are shown in Table 1-1, Table 1-2, and Table 2, and the evaluation results of the colored adhesive tapes for evaluation are shown in Table 3. It should be noted that each colored adhesive tape was prepared in A4 size.
[0096]
[0097]
[0098] [Table 2]
[0099]
[0100] (Example 1)
[0101] (1) Production of acrylic copolymer A (solution polymerization)
[0102] Ethyl acetate was added as a polymerization solvent to the reaction vessel, and after bubbling with nitrogen, the reaction vessel was heated while nitrogen was flowing in and reflux was started. Next, a polymerization initiator solution prepared by diluting 0.1 parts by weight of azobisisobutyronitrile as a polymerization initiator with ethyl acetate by 10 times was added to the reaction vessel, and 56.9 parts by weight of butyl acrylate, 40 parts by weight of 2-ethylhexyl acrylate, 3 parts by weight of acrylic acid and 0.1 parts by weight of 2-hydroxyethyl acrylate were added dropwise over 2 hours. After the dropwise addition was completed, a polymerization initiator solution prepared by diluting 0.1 parts by weight of azobisisobutyronitrile as a polymerization initiator with ethyl acetate by 10 times was added to the reaction vessel again, and a polymerization reaction was carried out for 4 hours to obtain a solution containing acrylic copolymer A.
[0103] The obtained solution containing the acrylic copolymer A was diluted 50 times with tetrahydrofuran (THF) by filtering through a filter (material: polytetrafluoroethylene, pore size: 0.2 μm) to prepare a measurement sample. The measurement sample was supplied to a gel permeation chromatograph (manufactured by Waters, 2690 Separations Model) and GPC measurement was performed under the conditions of a sample flow rate of 1 ml / min and a column temperature of 40° C. The polystyrene-equivalent molecular weight of the acrylic copolymer A was measured and the weight average molecular weight was found to be 1.28 million.
[0104] To the obtained solution containing the acrylic copolymer A, 25 parts by weight of a polymerized rosin ester (Pensel D-135 manufactured by Arakawa Chemical Industries, Ltd.) as a tackifier resin and 4 parts by weight of an isocyanate crosslinking agent (Takenate D-101E manufactured by Mitsui Chemicals, Inc.) were added based on 100 parts by weight of the acrylic copolymer A to obtain an acrylic adhesive (hereinafter referred to as acrylic adhesive a).
[0105] (2) Manufacture of colored adhesive tape
[0106] A PET film was prepared as a resin film layer, and a coating material for forming a coloring layer was applied to one side of the resin film layer using a rod coater. The specification of the wire rod used at this time was #8. After coating, it was dried in an oven at 80°C for 2 minutes to form a coloring layer. The thickness of the coloring layer after drying was 2.5 μm.
[0107] Next, a coating for forming a matte layer was applied to the other side of the resin film layer having a colored layer formed on one side using a rod coater. The specification of the wire rod used at this time was #5. After coating, it was dried in an oven at 80°C for 2 minutes and then aged in an oven at 40°C for 1 day to form a matte layer. The thickness of the matte layer after aging was 1.5 μm.
[0108] Next, a PET film with a thickness of 38 μm and a silicone release treatment surface was prepared as a release film, and an acrylic adhesive for forming an adhesive layer was applied to the silicone release treatment surface of the release film using an applicator. After coating, it was dried in an oven at 110° C. for 2 minutes to form an adhesive layer. The thickness of the adhesive layer was 2 μm.
[0109] Next, the colored layer side surface of the resin film layer and the adhesive layer side surface of the release film were faced to each other, and they were bonded together with a roller, and then aged in an oven at 40° C. for 2 days. Thus, a colored adhesive tape consisting of a laminate of “matte layer / resin film layer / colored layer / adhesive layer / release film” was obtained.
[0110] At this time, the following materials were used as the coating material for forming the matte layer, the resin film layer, the coating material for forming the coloring layer, the acrylic adhesive for forming the adhesive layer, and the release film.
[0111] Matt layer
[0112] Resin: Polyester resin (Vylon 200, manufactured by Toyobo Co., Ltd.)
[0113] Isocyanate: Aliphatic isocyanate HDI
[0114] Matting agent: Silicon dioxide (SYLOPHOBIC 100, manufactured by Fuji Silysia Chemical Co., Ltd.)
[0115] Pigment: None
[0116] Solvent: "Toluene: MEK = 1:1"
[0117] Formula: "Resin: isocyanate: matting agent: solvent: pigment = 20:3:5:72:0"
[0118] Resin film layer
[0119] 2 μm polyester film (Lumirror 2-F51, manufactured by Toray Industries, Inc.)
[0120] Coloring Layer
[0121] Resin: Polyester resin (Vylon 200, manufactured by Toyobo Co., Ltd.)
[0122] Isocyanate: Aliphatic isocyanate HDI
[0123] Pigment: Carbon black
[0124] Solvent: "Toluene: MEK = 1:1"
[0125] Mixture: "Resin: Isocyanate: Pigment: Solvent = 20:3:15:62"
[0126] Adhesive layer
[0127] Acrylic adhesive
[0128] The gel fraction of the adhesive layer obtained from the acrylic adhesive a was measured by the method of formula (1) and found to be 35%. The glass transition temperature (Tg) was measured by the following method and found to be 3°C.
[0129] The glass transition temperature (Tg) of the adhesive layer obtained from the acrylic adhesive a was measured using a polymer dynamic viscoelasticity measuring apparatus "itkDVA-200" (manufactured by IT Instruments and Controls Co., Ltd.) under the following conditions to measure the storage modulus G' and loss modulus G" at each temperature, calculate tanδ at each temperature, and measure the temperature at which tanδ reaches a peak as Tg.
[0130] Measurement mode: Shear
[0131] Heating rate: 5℃ / min
[0132] Measuring temperature range: -30~150℃
[0133] Set strain: 0.1%
[0134] Vibration frequency: 1Hz
[0135] The measurement sample was prepared by heating and drying the acrylic adhesive a and aging it under the same conditions as when forming the adhesive layer, and then molding the final sample into a shape of 1 mm in thickness, 6 mm in width, and 10 mm in length.
[0136] Release film
[0137] Silicone release treated PET film (SP3000, manufactured by TOYOCLOTH Co., Ltd.)
[0138] (Example 2)
[0139] A colored pressure-sensitive adhesive tape was obtained by the same procedure as in Example 1 except that the coating material for forming a colored layer was changed. The materials of the coating material for forming a colored layer in Example 2 are as follows.
[0140] Coloring Layer
[0141] Resin: Polyester resin (Vylon 200, manufactured by Toyobo Co., Ltd.)
[0142] Isocyanate: Aliphatic isocyanate HDI
[0143] Pigment: 15 parts carbon black, 1 part phthalocyanine blue
[0144] Solvent: "Toluene: MEK = 1:1"
[0145] Formula: "Resin: Isocyanate: Pigment: Solvent = 20:3:16:62"
[0146] (Example 3)
[0147] A colored pressure-sensitive adhesive tape was obtained by the same procedure as in Example 1 except that the coating material for forming a colored layer was changed. The materials of the coating material for forming a colored layer in Example 3 are as follows.
[0148] Coloring Layer
[0149] Resin: Acrylic resin
[0150] Isocyanate: Aliphatic isocyanate HDI
[0151] Pigment: Carbon black
[0152] Solvent: "Toluene: MEK = 1:1"
[0153] Formula: "Resin: Isocyanate: Pigment: Solvent = 20:3:16:62"
[0154] (Example 4)
[0155] A colored pressure-sensitive adhesive tape was obtained by the same procedure as in Example 1 except that the material of the coating material for forming the matte layer was changed. The material of the coating material for forming the matte layer in Example 4 is as follows.
[0156] Matt layer
[0157] Resin: Polyester resin (Vylon 200, manufactured by Toyobo Co., Ltd.)
[0158] Isocyanate: Aliphatic isocyanate HDI
[0159] Matting agent: Silicon dioxide (SYLOPHOBIC 100, manufactured by Fuji Silysia Chemical Co., Ltd.)
[0160] Pigment: Carbon black
[0161] Solvent: "Toluene: MEK = 1:1"
[0162] Formula: "Resin: isocyanate: matting agent: solvent: pigment = 20:3:5:72:1"
[0163] (Example 5)
[0164] A colored pressure-sensitive adhesive tape was obtained by the same procedure as in Example 1 except that the amount of the coating material for forming the matte layer was changed. In Example 5, a matte layer was formed by the following procedure.
[0165] On the other side of the resin film layer with the color layer formed on one side, a coating for forming a matte layer was applied using a rod coater. The specification of the wire rod used at this time was #8. After coating, it was dried in an oven at 80°C for 2 minutes and then aged in an oven at 40°C for 1 day to form a matte layer. The thickness of the matte layer after aging was 3.0 μm.
[0166] (Example 6)
[0167] A colored pressure-sensitive adhesive tape was obtained by the same procedure as in Example 1 except that the amount of the coating material for forming the matte layer was changed. In Example 6, a matte layer was formed by the following procedure.
[0168] On the other side of the resin film layer with the color layer formed on one side, a coating for forming a matte layer was applied using a rod coater. The specification of the wire rod used at this time was #3. After coating, it was dried in an oven at 80°C for 2 minutes and then aged in an oven at 40°C for 1 day to form a matte layer. The thickness of the matte layer after aging was 0.5μm.
[0169] (Examples 7 to 12)
[0170] In Example 1, a colored adhesive tape was obtained by the same procedure as in Example 1 except that the adhesive used to form the adhesive layer was different. In Examples 7 to 12, the adhesives shown in Table 1-2 were used as the adhesives used to form the adhesive layer. That is, in Examples 7 to 12, acrylic adhesives b to g were used as the adhesives used to form the adhesive layer. These acrylic adhesives b to g were prepared according to the following procedures.
[0171] (1-1) Production of Acrylic Copolymer B (Solution Polymerization)
[0172] Ethyl acetate was added as a polymerization solvent to the reaction vessel, and after bubbling with nitrogen, the reaction vessel was heated while nitrogen was flowing in and reflux was started. Next, a polymerization initiator solution prepared by diluting 10 times 0.1 parts by weight of azobisisobutyronitrile with ethyl acetate as a polymerization initiator was added to the reaction vessel, and 96.6 parts by weight of n-heptyl acrylate, 2.9 parts by weight of acrylic acid and 0.5 parts by weight of 2-hydroxyethyl acrylate were added dropwise over 2 hours. After the dropwise addition was completed, a polymerization initiator solution prepared by diluting 10 times 0.1 parts by weight of azobisisobutyronitrile with ethyl acetate as a polymerization initiator was added to the reaction vessel again, and a polymerization reaction was carried out for 4 hours to obtain a solution containing acrylic copolymer B.
[0173] The obtained solution containing the acrylic copolymer B was diluted 50 times with tetrahydrofuran (THF) by filtering through a filter (material: polytetrafluoroethylene, pore size: 0.2 μm) to prepare a measurement sample. The measurement sample was supplied to a gel permeation chromatograph (manufactured by Waters, 2690 Separations Model) and subjected to GPC measurement under the conditions of a sample flow rate of 1 ml / min and a column temperature of 40° C. The polystyrene-equivalent molecular weight of the acrylic copolymer B was measured and the weight average molecular weight was found to be 1,000,000.
[0174] To the obtained solution containing the acrylic copolymer B, 14 parts by weight of a polymerized rosin ester (hydroxyl value: 46, softening point: 152° C.) as a tackifier resin, 10 parts by weight of a hydrogenated rosin ester (KE359 manufactured by Arakawa Chemical Industries, Ltd.), 10 parts by weight of a terpene phenol (G150 manufactured by Yasuhara Chemical Co., Ltd.) and 0.5 parts by weight of an isocyanate crosslinking agent (Takenate D-101E manufactured by Mitsui Chemicals, Inc.) were added based on 100 parts by weight of the acrylic copolymer B to obtain an acrylic adhesive (hereinafter referred to as acrylic adhesive b).
[0175] The gel fraction of the adhesive layer obtained from the acrylic adhesive b was measured by the method of formula (1) and found to be 35%. The glass transition temperature (Tg) of the adhesive layer was measured by the same method as in Example 1 and found to be -8°C.
[0176] (1-2) Production of Acrylic Copolymer C (Solution Polymerization)
[0177] Ethyl acetate was added as a polymerization solvent to the reaction vessel, and after bubbling with nitrogen, the reaction vessel was heated while nitrogen was flowing in and reflux was started. Next, a polymerization initiator solution prepared by diluting 10 times 0.1 parts by weight of azobisisobutyronitrile with ethyl acetate as a polymerization initiator was added to the reaction vessel, and 95.1 parts by weight of n-heptyl acrylate, 4.8 parts by weight of acrylic acid, and 0.1 parts by weight of 2-hydroxyethyl acrylate were added dropwise over 2 hours. After the dropwise addition was completed, a polymerization initiator solution prepared by diluting 10 times 0.1 parts by weight of azobisisobutyronitrile with ethyl acetate as a polymerization initiator was added to the reaction vessel again, and a polymerization reaction was carried out for 4 hours to obtain a solution containing acrylic copolymer C.
[0178] The obtained solution containing the acrylic copolymer C was diluted 50 times with tetrahydrofuran (THF) and filtered through a filter (material: polytetrafluoroethylene, pore size: 0.2 μm) to prepare a measurement sample. The measurement sample was supplied to a gel permeation chromatograph (manufactured by Waters, 2690 Separations Model) and GPC measurement was performed under the conditions of a sample flow rate of 1 ml / min and a column temperature of 40° C. The polystyrene-equivalent molecular weight of the acrylic copolymer C was measured and the weight average molecular weight was found to be 1.2 million.
[0179] To the obtained solution containing acrylic copolymer C, 14 parts by weight of polymerized rosin ester (hydroxyl value: 46, softening point: 152° C.) as a tackifier resin, 10 parts by weight of hydrogenated rosin ester (KE359 manufactured by Arakawa Chemical Industries, Ltd.), 10 parts by weight of terpene phenol (G150 manufactured by Yasuhara Chemical Co., Ltd.) and 2.5 parts by weight of an isocyanate crosslinking agent (Takenate D-101E manufactured by Mitsui Chemicals, Inc.) were added based on 100 parts by weight of acrylic copolymer C to obtain an acrylic adhesive (hereinafter referred to as acrylic adhesive c).
[0180] The gel fraction of the adhesive layer obtained from the acrylic adhesive c was measured by the method of formula (1) and found to be 35%. The glass transition temperature (Tg) of the adhesive layer was measured by the same method as in Example 1 and found to be -1°C.
[0181] To the obtained solution containing acrylic copolymer C, 24 parts by weight of polymerized rosin ester (hydroxyl value: 46, softening point: 152° C.) as a tackifier resin, 10 parts by weight of terpene phenol (G150 manufactured by Yasuhara Chemical Co., Ltd.) and 2.5 parts by weight of an isocyanate crosslinking agent (Takenate D-101E manufactured by Mitsui Chemicals, Inc.) were added based on 100 parts by weight of acrylic copolymer C to obtain an acrylic adhesive (hereinafter referred to as acrylic adhesive d).
[0182] The gel fraction of the adhesive layer obtained from the acrylic adhesive d was measured by the method of formula (1) and found to be 30%. The glass transition temperature (Tg) of the adhesive layer was measured by the same method as in Example 1 and found to be 0°C.
[0183] To the obtained solution containing the acrylic copolymer C, 14 parts by weight of a polymerized rosin ester (hydroxyl value: 46, softening point: 152° C.) as a tackifier resin, 10 parts by weight of a hydrogenated rosin ester (KE359 manufactured by Arakawa Chemical Industries, Ltd.), 10 parts by weight of a terpene phenol (G150 manufactured by Yasuhara Chemical Co., Ltd.) and 0.1 parts by weight of an epoxy crosslinking agent (A-EX manufactured by Soken Chemical Co., Ltd., solid content 5%) were added based on 100 parts by weight of the acrylic copolymer C to obtain an acrylic adhesive (hereinafter referred to as acrylic adhesive e).
[0184] The gel fraction of the adhesive layer obtained from the acrylic adhesive e was measured by the method of formula (1) and found to be 55%. The glass transition temperature (Tg) of the adhesive layer was measured by the same method as in Example 1 and found to be 1°C.
[0185] To the obtained solution containing the acrylic copolymer C, 14 parts by weight of a polymerized rosin ester (hydroxyl value: 46, softening point: 152° C.) as a tackifier resin, 10 parts by weight of a hydrogenated rosin ester (KE359 manufactured by Arakawa Chemical Industries, Ltd.), 10 parts by weight of a terpene phenol (G150 manufactured by Yasuhara Chemical Co., Ltd.), 1.2 parts by weight of an isocyanate crosslinking agent (Takenate D-101E manufactured by Mitsui Chemicals, Inc.) and 0.05 parts by weight of an epoxy crosslinking agent (A-EX manufactured by Soken Chemical Co., Ltd., solid content 5%) were added based on 100 parts by weight of the acrylic copolymer C to obtain an acrylic adhesive (hereinafter referred to as acrylic adhesive f).
[0186] The gel fraction of the adhesive layer obtained from the acrylic adhesive f was measured by the method of formula (1) and found to be 65%. The glass transition temperature (Tg) of the adhesive layer was measured by the same method as in Example 1 and found to be 2°C.
[0187] To the obtained solution containing acrylic copolymer C, 14 parts by weight of polymerized rosin ester (hydroxyl value: 46, softening point: 152° C.) as a tackifier resin, 10 parts by weight of hydrogenated rosin ester (KE359 manufactured by Arakawa Chemical Industries, Ltd.), 10 parts by weight of terpene phenol (G150 manufactured by Yasuhara Chemical Co., Ltd.), 2.5 parts by weight of an isocyanate crosslinking agent (Takenate D-101E manufactured by Mitsui Chemicals, Inc.) and 1 part by weight of a pigment (Multilac A903 manufactured by Dainichi Seika Industries, Ltd., solid content 55%) were added based on 100 parts by weight of the acrylic copolymer C to obtain an acrylic adhesive (hereinafter referred to as acrylic adhesive g).
[0188] The gel fraction of the adhesive layer obtained from the acrylic adhesive g was measured by the method of formula (1) and found to be 35%. The glass transition temperature (Tg) of the adhesive layer was measured by the same method as in Example 1 and found to be -1°C.
[0189] (Comparative Example 1)
[0190] A colored pressure-sensitive adhesive tape was produced by the same procedure as in Example 1 except that the amount of the coating material for forming the matte layer was changed. In Comparative Example 1, a matte layer was formed by the following procedure.
[0191] On the other side of the resin film layer with the color layer formed on one side, the following matte layer forming coating was applied using a rod coater. The specification of the wire rod used at this time was #3. After coating, it was dried in an oven at 80°C for 2 minutes and then aged in an oven at 40°C for 1 day to form a matte layer. The thickness of the matte layer after aging was 0.3μm.
[0192] Matt layer
[0193] Resin: Polyester resin (Vylon 200, manufactured by Toyobo Co., Ltd.)
[0194] Isocyanate: Aliphatic isocyanate HDI
[0195] Matting agent: Silicon dioxide (SYLOPHOBIC 100, manufactured by Fuji Silysia Chemical Co., Ltd.)
[0196] Pigment: None
[0197] Solvent: "Toluene: MEK = 1:1"
[0198] Formula: "Resin: isocyanate: matting agent: solvent: pigment = 20:3:5:90:0"
[0199] (Comparative Example 2)
[0200] In Example 1, a colored adhesive tape was produced by the same procedure as in Example 1 except that the lamination order of the colored layer and the resin film layer was changed. In Comparative Example 2, a colored adhesive tape was produced by the following procedure.
[0201] A PET film was prepared as a resin film layer, and a coating material for forming a coloring layer was applied to one side of the resin film layer using a rod coater. The specification of the wire rod used at this time was #8. After coating, it was dried in an oven at 80°C for 2 minutes to form a coloring layer. The thickness of the coloring layer after drying was 2.5 μm.
[0202] Next, a coating material for forming a matte layer was applied on the colored layer using a rod coater. The specification of the wire rod used at this time was #5. After coating, it was dried in an oven at 80°C for 2 minutes and then aged in an oven at 40°C for 1 day to form a matte layer. The thickness of the matte layer after aging was 1.5 μm.
[0203] Next, a PET film with a thickness of 38 μm and a silicone release treatment surface was prepared as a release film, and an acrylic adhesive for forming an adhesive layer was applied to the silicone release treatment surface of the release film using an applicator. After coating, it was dried in an oven at 110° C. for 2 minutes to form an adhesive layer. The thickness of the adhesive layer was 2 μm.
[0204] Next, the colored layer side surface of the resin film layer and the adhesive layer side surface of the release film were faced to each other, and they were bonded together with a roller, and then aged in an oven at 40° C. for 2 days. Thus, a colored adhesive tape consisting of a laminate of “matte layer / colored layer / resin film layer / adhesive layer / release film” was obtained.
[0205] (Comparative Example 3)
[0206] In Example 1, a colored pressure-sensitive adhesive tape was produced by the same procedure as in Example 1 except that the matte layer was not provided. In Comparative Example 3, a colored pressure-sensitive adhesive tape was produced by the following procedure.
[0207] A PET film was prepared as a resin film layer, and a coating material for forming a coloring layer was applied to one surface of the resin film layer using a rod coater. The specification of the wire rod used at this time was #8. After coating, it was dried in an oven at 80°C for 2 minutes to form a coloring layer. The thickness of the coloring layer after drying was 2.5 μm.
[0208] Next, a PET film with a thickness of 38 μm and a silicone release treatment surface was prepared as a release film, and a coating for forming an adhesive layer was applied to the silicone release treatment surface of the release film using an applicator. After coating, it was dried in an oven at 110° C. for 2 minutes to form an adhesive layer. The thickness of the adhesive layer was 2 μm.
[0209] Next, the colored layer side surface of the resin film layer and the adhesive layer side surface of the release film were faced to each other, and they were bonded together with a roller, and then aged in an oven at 40° C. for 2 days. Thus, a colored adhesive tape consisting of a laminate of “resin film layer / colored layer / adhesive layer / release film” was obtained.
[0210] (Evaluation method)
[0211] The colored pressure-sensitive adhesive tapes for evaluation of Examples 1 to 12 and Comparative Examples 1 to 3 were evaluated in terms of total film thickness, transmittance, gloss value, surface condition, and hue.
[0212] (Total film thickness)
[0213] The thickness of the entire colored pressure-sensitive adhesive tape was measured as the total film thickness.
[0214] Regarding the total film thickness, a case where the thickness was 5 μm or more and less than 10 μm was marked as ○, and a case where the thickness was outside the range was marked as ×.
[0215] (Transmittance)
[0216] The light transmittance (total light transmittance) of the laminated body after removing the release film from each colored pressure-sensitive adhesive tape was measured. The light transmittance was measured in accordance with JIS K7105 using "HR-100" manufactured by Murakami Color Research Laboratory.
[0217] The case where the light transmittance was 5% or less was marked as ○, and the case where the light transmittance was greater than 5% was marked as ×.
[0218] (Gloss value)
[0219] The gloss value of the matte layer-side surface of the colored pressure-sensitive adhesive tape was measured using a commercially available gloss meter (eg, "Gloss Checker IG-410" manufactured by Horiba, Ltd.) at a measurement angle of 60°.
[0220] The case where the gloss value at a measurement angle of 60° was 3.0 or less was evaluated as ○, and the case where the gloss value was greater than 3.0 was evaluated as ×.
[0221] (Surface condition)
[0222] The surface of the colored pressure-sensitive adhesive tape opposite to the release film was visually observed to evaluate the surface condition of the colored pressure-sensitive adhesive tape. The surface of the colored pressure-sensitive adhesive tape was evaluated for uniformity and unevenness.
[0223] The case where the surface of the colored pressure-sensitive adhesive tape was uniform was evaluated as ○, and the case where the surface of the colored pressure-sensitive adhesive tape was non-uniform or had uneven depth was evaluated as ×.
[0224] (Hue)
[0225] The hue of the colored pressure-sensitive adhesive tape surface was visually observed, and the difference in hue from the colored pressure-sensitive adhesive tape in Example 1 was observed.
[0226]
[0227] As shown in Table 3, for the colored adhesive tapes of Examples 1 to 12 having a structure in which a matte layer, a resin film layer, a colored layer, an adhesive layer, and a release film are stacked in order from the release film side, and the thickness of the matte layer satisfies 0.5 μm or more and 3 μm or less, the light transmittance is 2.5%, and the 60° gloss value is 1.5 in Examples 1 to 4 and Examples 7 to 12, 0.9 in Example 5, and 2.9 in Example 6, and it is confirmed that the color tone, texture, and matte feeling are good, and the surface is uniform and has no uneven depth. In addition, as shown in Examples 7 to 12, even when the components constituting the adhesive layer are different, it is confirmed that the color tone, texture, and matte feeling are good, and the surface is uniform and has no uneven depth.
[0228] In addition, in the colored adhesive tape of Example 2, not only carbon black but also phthalocyanine blue is used as the pigment of the colored layer, so the blue feeling of the obtained colored adhesive tape is increased. In addition, it is confirmed that even in the case of Example 3 in which an acrylic resin is used as the colored layer instead of a polyester resin, the same effect as that of Example 1 in which a polyester resin is used is obtained. In the case of using an acrylic resin, further improvement in adhesion can also be expected. In addition, it is confirmed that for Example 4 in which carbon black is added as a pigment to the matte layer, the black feeling is increased compared to the colored adhesive sheet of Example 1 in which no pigment is added to the matte layer.
[0229] In addition, in the case of Comparative Example 1 in which the thickness of the matte layer is 0.3 μm, the 60° gloss value is large, so it is difficult to obtain a matte feeling, and the inspection light source used in defect inspection is reflected on the surface of the matte layer, so it is difficult to find defects. On the other hand, in the case of Example 5 in which the thickness of the matte layer is 3.0 μm, a sufficient matte feeling is obtained.
[0230] In addition, in the colored adhesive tape of Comparative Example 2 in which a matte layer is directly laminated on a colored layer, the surface of the colored layer in contact with the matte layer becomes rough due to the influence of the solvent in the matte layer. As a result, the surface of the colored adhesive tape opposite to the release film, that is, the surface on the matte layer side, has many uneven depths and the design property is reduced.
[0231] In addition, in the colored adhesive tape of Comparative Example 3 in which a matte layer was not provided, the gloss value was 113, and a matte feeling was not obtained. Moreover, the inspection light source used in defect inspection was reflected on the surface of the resin film layer, so defects were less likely to be found than in Comparative Example 1.
[0232] In addition, about Examples 1 to 4, the water contact angle was measured according to JIS R 3257:1999, and the result was 105 degrees, and it was confirmed that the antifouling property was sufficiently high.
[0233] It should be noted that the present invention can take the following configurations, for example.
[0234] (1) A colored adhesive tape, characterized in that it is a colored adhesive tape in which a release film, an adhesive layer, a colored layer, a resin film layer and a matte layer are laminated in this order,
[0235] The matting layer is a layer having a thickness of 0.5 μm or more and 3 μm or less and mainly composed of a polyester resin, an isocyanate and a matting agent, wherein the matting agent contains silicon dioxide.
[0236] The coloring layer is a layer containing a resin, isocyanate, and a pigment including carbon black as main components.
[0237] (2) The colored adhesive tape according to (1) above, wherein the light transmittance of the laminate of the adhesive layer, the colored layer, the resin film layer, and the matte layer is 5% or less.
[0238] (3) The colored pressure-sensitive adhesive tape according to (1) or (2) above, wherein the 60° gloss value of the surface on the matte layer side is 3 or less.
[0239] (4) The colored pressure-sensitive adhesive tape according to any one of (1) to (3) above, wherein the matte layer is colored.
[0240] (5) The colored pressure-sensitive adhesive tape according to any one of (1) to (4) above, which is used for surface protection of a heat sink.
[0241] (6) The colored pressure-sensitive adhesive tape according to any one of (1) to (4) above, which is used for surface protection of a magnetic sheet.
[0242] Description of Reference Numerals
[0243] 1 Colored adhesive tape
[0244] 2 Matting layer
[0245] 3 Resin film layer
[0246] 4 Coloring Layers
[0247] 5 Adhesive layer
[0248] 6. Peel film
[0249] 10 Heat sink or magnetic sheet
Claims
1. A colored adhesive tape, characterized in that: It is a colored adhesive tape having a release film, an adhesive layer, a colored layer, a resin film layer and a matte layer laminated in this order. The matting layer is a layer having a thickness of 0.5 μm or more and 3 μm or less, and mainly composed of a polyester resin, an isocyanate and a matting agent, wherein the matting agent contains silicon dioxide. The coloring layer is a layer containing a resin, isocyanate, and a pigment including carbon black as main components.
2. The colored adhesive tape according to claim 1, characterized in that The light transmittance of the laminate of the adhesive layer, the colored layer, the resin film layer, and the matte layer is 5% or less.
3. The colored adhesive tape according to claim 1 or 2, characterized in that: The 60° gloss value of the surface on the matte layer side is 3 or less.
4. The colored adhesive tape according to claim 1 or 2, characterized in that: The matte layer is colored.
5. The colored adhesive tape according to claim 1 or 2, characterized in that: It is used for surface protection of heat sinks.
6. The colored adhesive tape according to claim 1 or 2, characterized in that: It is used for surface protection of magnetic sheets.